A New One‐Pot Fluorescence Derivatization Strategy for Highly Sensitive MicroRNA Analysis - Pan, Li; Zhang, Huaisheng; Zhao, Jingjin; Ogungbe, Ifedayo Victor; Zhao, Shulin; Liu, Yi‐Ming (Chemistry : a European journal, 2020)
MicroRNAs (miRNAs) modulate the expression of over 30 % of mammalian genes during development and apoptosis, and abnormal expression of miRNAs may lead to a range of human pathologies. Therefore, analysis of miRNAs is valuable for disease diagnostics. In this work, a novel one‐pot fluorescence derivatization strategy was developed for miRNA analysis. The mechanism of the derivatization reaction was explored by using instrumental methods, including liquid chromatography, fluorescence spectroscopy, and mass spectrometry. Highly fluorescent N6‐ethenoadenine (ϵ‐adenine) was formed and detached from the miRNA sequence through the reaction of adenine in nucleic acids with 2‐chloroacetaldehyde (CAA) at 100 °C. This is the first experimental evidence that the cooperation of formed ϵ‐adenine and water‐mediated hydrogen‐bond interaction between the proton at the 2′‐ and the oxyanion at 3′‐positions stabilized the oxocarbenium significantly, which makes the depurination and derivatization of miRNA highly effective. Based on this derivatization strategy, a facile and sensitive high‐performance liquid chromatography method was developed for quantitative assay of miRNAs. In combination with magnetic solid‐phase extraction (MSPE), the HPLC method was shown to be useful for the determination of microRNAs at sub‐picomolar level in serum samples. microRNAs made easy: A one‐pot fluorescence derivatization strategy has been developed for highly sensitive microRNA analysis. Based on this derivatization strategy, a facile and sensitive high‐performance liquid chromatography method was developed for quantitative assay of microRNAs.